Modelling the lifetime cost-effectiveness of catheter ablation for atrial fibrillation with heart failure - Lan Gao; Marj Moodie (BMJ Open)
Objectives Assessing the cost-effectiveness credentials of this intervention in patients with concomitant atrial fibrillation (AF) and heart failure (HF) compared with usual medical therapy.Design A Markov model comprising two health states (ie, alive or dead) was constructed. The transition probabilities were directly derived from published Kaplan-Meier curves of the pivotal randomised controlled trial and extrapolated over the cohort’s lifetime using recommended methods. Costs of catheter ablation, outpatient consultations, hospitalisation, medications and examinations were included. Resource use and unit costs were sourced from government websites or published literature. A lifetime horizon and a healthcare system perspective were taken. All costs and benefits were discounted at 3% annually. Deterministic (DSA) and probabilistic sensitivity analyses (PSA) were run around the key model parameters to test the robustness of the base case results.Participants A hypothetical Australian cohort of patients with concomitant AF and HF who are resistant to antiarrhythmic treatment.Interventions Catheter ablation versus medical therapy.Results The catheter ablation was associated with a cost of $A44 377 per person, in comparison to $A28 506 for the medical therapy alone over a lifetime. Catheter ablation contributed to 4.58 quality-adjusted life years (QALYs) and 6.99 LY gains compared with 4.30 QALYs and 6.53 LY gains, respectively, in the medical therapy arm. The incremental cost-effectiveness ratio was $A55 942/QALY or $A35 020/LY. The DSA showed that results were highly sensitive to costs of ablation and time horizon. The PSA yielded very consistent results with the base case.Conclusions Offering catheter ablation procedure to patients with systematic paroxysmal or persistent AF who failed to respond to antiarrhythmic drugs was associated with higher costs, greater benefits. When compared with medical therapy alone, this intervention is not cost-effective from an Australia healthcare system perspective.